2015
DOI: 10.1039/c5ob01573a
|View full text |Cite
|
Sign up to set email alerts
|

Practical isolation of polygodial from Tasmannia lanceolata: a viable scaffold for synthesis

Abstract: Polygodial, a valuable sesquiterpene dialdehyde featuring an epimerizable stereocenter was efficiently extracted and isolated in gram-scale quantities (3.3% w/w) from Tasmannia lanceolata (Tasmanian native pepper) via a recently developed rapid pressurised hot water extraction (PHWE) technique that utilises an unmodified household espresso machine. This method was compared to the maceration of T. lanceolata under a range of conditions. Polygodial was used to achieve semi-syntheses of closely related sesquiterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 40 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…Furthermore, during the extraction process, epoxide ring‐opening of potentially reactive functional groups was not observed (as determined by 1 H NMR analysis of the crude extracts containing coumarins 6–9 ). This underscores the mildness of this extraction technique and is consistent with previous observations in our germane studies on the isolation of natural products 2 and 4 featuring somewhat sensitive functional groups . Therefore, we have demonstrated that the PHWE methodology that we have developed is amenable to the efficient identification of plant species that can provide complex organic scaffolds that are potentially useful synthetically.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, during the extraction process, epoxide ring‐opening of potentially reactive functional groups was not observed (as determined by 1 H NMR analysis of the crude extracts containing coumarins 6–9 ). This underscores the mildness of this extraction technique and is consistent with previous observations in our germane studies on the isolation of natural products 2 and 4 featuring somewhat sensitive functional groups . Therefore, we have demonstrated that the PHWE methodology that we have developed is amenable to the efficient identification of plant species that can provide complex organic scaffolds that are potentially useful synthetically.…”
Section: Resultssupporting
confidence: 89%
“…Active ingredients were extracted from BM (Chinese variety; sourced from local vegetable super market in Hobart, Tasmania, Australia labelled as bitter melon) by pressurised hot water using a modification of a method previously described for natural product isolation [27, 28]. …”
Section: Methodsmentioning
confidence: 99%
“…PHWE (35% v/v EtOH/H 2 O) facilitated the isolation of gramscale quantities of the drimane dialdehyde polygodial (39; 3.3% w/w) from Tasmanian pepperberry leaves (Tasmannia lanceolata) (Figure 11). [41] Access to synthetically-useful quantities of chiral scaffold 39 by this approach allowed for the preparation of related natural products via semi-synthesis, [41] novel Nheterocycles, [42] and new biologically-active molecules. [43,44] PHWE was found to be superior in extraction efficiency when directly compared to a commercial ASE system.…”
Section: Coumarins Terpenoids and Essential Oilsmentioning
confidence: 99%
“…[43,44] PHWE was found to be superior in extraction efficiency when directly compared to a commercial ASE system. [41] Specifically, the optimal extraction temperature and solvent system (EtOH/ H 2 O) parameters for the extraction of polygodial from T. lanceolata were determined for the ASE system, with varying ethanol/water solvent mixtures (15%, 25%, and 35% v/v EtOH/ H 2 O), and temperatures (70°C, 90°C, 110°C, 130°C). The optimal extraction conditions (90°C using 35% v/v EtOH/H 2 O) are consistent with the PHWE conditions.…”
Section: Coumarins Terpenoids and Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation